Mutagenesis of the regulatory domain of phenylalanine hydroxylase - Wang, Guo-An (The National Academy of Sciences, 2001)
The regulatory domain of phenylalanine hydroxylase (PAH, EC 1.14.16.1) consists of more than 100 amino acids at the N terminus, the removal of which significantly activates the enzyme. To study the regulatory properties controlled by the N terminus, a series of truncations and site-specific mutations were made in this region of rat PAH. These enzymes were expressed highly in Escherichia coli and purified through a pterin-conjugated Sepharose affinity column. The removal of the first 26 amino acids of the N terminus increased the activity by about 20-fold, but removal of the first 15 amino acids increased the activity by only 2-fold. Replacing serine-29 of rat PAH with cysteine from the same site of human PAH increased the activity by more than 4-fold. Mutation of serine to other amino acids with varying side chains: alanine, methionine, leucine, aspartic acid, asparagine, and arginine also resulted in significant activation, indicating a serine-specific inhibitory effect. But these site-specific mutants showed 30–40% lower activity when assayed with 6-methyl-5,6,7,8-tetrahydropterin. Stimulation of hydroxylase activity by preincubation of the enzyme with phenylalanine was inversely proportional to the activation state of all these mutants. Combined with recent crystal structures of PAH [Kobe, B. et al. (1999) Nat. Struct. Biol. 6, 442–448; and Erlandsen, H., Bjorgo, E., Flatmark, T. & Stevens, R. C. (2000) Biochemistry 39, 2208–2217], these data suggest that residues 16–26 have a controlling regulatory effect on the activity by interaction with the dihydroxypropyl side chain of (6R)-5,6,7,8-tetrahydrobiopterin. The serine/cysteine switch explains the difference in regulatory properties between human and rat PAH. The N terminus as a whole is important for maintaining rat PAH in an optimum catalytic conformation.